JUGGLING AS A MEANS OF MOTOR ACTIVITY DURING DISTANCE EDUCATION (Physical Culture and Sport: Scientific Perspective, 2024)
In remote education, empowering higher education students through independent physical activities has never been more essential. Juggling is an enjoyable exercise that requires neither specialized areas nor hefty investments in equipment. This festive mix of physical development and enjoyment motivates young minds to embrace active living.This paperwork aims to inspire students' physical activity through the art of juggling, a versatile exercise tailored to individual tastes. Over a specified period, students will start a journey to master juggling skills, with the freedom to expand their challenge by increasing the number of balls, aligning with their appeals and abilities.While many sports require specific physical skills, juggling reveals many remarkable, overlooked benefits. It enhances muscle strength, endurance, joint flexibility, and cardiovascular health while fostering arm sensitivity and finger coordination. Moreover, it facilitates the ability to defocus attention, perceive multiple objects simultaneously, and develop spatial awareness.Integrating juggling into the higher education agenda is a valuable recommendation for tutors. It upgrades the effectiveness of physical education and promotes a healthy lifestyle culture.Furthermore, juggling cultivates a sense of rhythm in students, develops their ability to make quick decisions, and trains their dexterity. The learning process requires mastering technique coordination and perseverance in the face of setbacks. Juggling allows students to see progress from a short perspective, which can be a great incentive to continue moving forward and maintain the rate of acquiring new skills.The playful nature of juggling, the wide variety of juggling objects, the varying levels of difficulty, and the possibility of teamwork — all of this has the potential to become a useful habit or a favorite hobby that can facilitate students' integration into the future workplace in modern life.
Keywords: juggling; students; distance learning; physical education; independent classes